Evaluasi Konfigurasi Bandar Udara Berdasarkan Standar RIB (Km No.44) Dengan Perhitungan Berdasarkan Annex 14, 2013 Serta ICAO AC No.150 E (Studi Kasus: Minangkabau International Airport) - Girang Rahmanul Hakim; Ari Sandhiyavitri; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Minangkabau International Airport has an annual growth rate of passengers and the aircraft operated there based on data from 2010 until 2016. The current runway has length 2750 m and largest type of aircraft is B 747 - 300. Minangkabau international airport has three taxiways 448 m x 30 m, 334 m x 30 m, and 305 m x 30 m and apron has dimensions 315 m x 120 m. The increase in air traffic has resulted in an evaluation of the airport configuration in present or future circumstances. Existing of the runway is an inadequate type of aircraft B 747 - 300 for international destination aircraft. As for the planning year, 2020 with the additional length of the enlarged base to 3000 m safely to use. Existing of taxiway is able to serve the plane. The apron for the existing state need to upgraded and the planning of 2020 should also be upgraded. At the peak hour of the plane for 2016 as many as 12 aircraft while the projection stage for 2035 obtained a peak hour of 28 this indicates Minangkabau International Airport will be developed later. Pavement for runways needs to be upgraded to the current state of affairs.Keywords: Airport Configuration, Evaluation, Projection